Açık hava reklamları ve reklam etkinliği ölçümü - Gelsev, Aslı (Fen Bilimleri Enstitüsü, 1994)
Bu çalışmada açık hava reklamları ve reklam etkinliği ölçümü olmak üzere iki temel konu bulunmaktadır. İlk bölümde esas konuya geçiş olması için reklam ve reklamın bazı özellikleri, çeşitleri ve fonksiyonları genel olarak anlatılmıştır. Bu arada başlıca medya türleri ve buralarda yayınlanan reklamlar da anlatılmıştır. Bu bölüm diğer medyalarda yayınlanan reklamlar ile açık hava reklamlarının karşılaştırılması açısından önem taşımaktadır. ikinci bölümde ise sadece açık hava reklamları, kullanılan medya türleri, özellikleri, açık hava reklamlarının üstün ve zayıf yanları ile Türkiye'deki uygulamalardan örnekler yer almaktadır. Üçüncü bölüm reklam etkinliğinin ölçülmesini ve haberleşme etkisini ölçen belli başlı yöntemleri içermektedir. Son bölümde de iki değişik araştırma sunulmaktadır. ilk olarak reklam sektörünün önde gelen ajanslarında yetkili kişilerle belirli bir soru dizini çerçevesinde görüşülmüştür. Verilen cevaplar bir rapor halinde aktarılmıştır. İkinci araştırmada ise ilan panolarının haberleşme etkinliği yardımlı ve yardımsız hatırlatma sorularını bir an ket formu ve 250 kişilik bir örnek kütle ile gerçekleştirilen bir daha çalışmasıdır. Bu araştırma izleyicilerin açık hava reklamlarını ne ölçüde hatırladıkları ve açık hava reklamlarına karşı tutum ve düşüncelerini ortaya çıkarmak amacıyla yapılmıştır.

Advertising in Promotion Mix Advertising consists of all the activities involved in presenting to a group a non personel oral or visual, openly sponsored message regarding a. product service or idea. The advertising message is disseminated through one or more media and is paid for by the identified sponsor. Advertising's two main objectives are (1) to inform the public about a firm and its products and (2) to persuade potential buyers that the firms products are better then those of its competitiors. Most companies expect advertising to increase sales and profits. The objectives can be achieved by providing useful information by changing consumer attitudes, and by showing how the firm's products or services can satisfy consumer needs. Some major advertising specific objectives are as follows : - Support personel selling - Improve dealer relations - Enter a new geographic marker or attract a new group of customers - Introduce a new product - Increase sales of a product - Expand the industry's sales - Build goodwill for the company -VII- The Major Types of Advertising 1. Institutional advaertising; designed to create a proper attitude toward the seller and to build goodwill, rather than to sell a specific product or service. 2. Primary and selective demand advertising; primary demand advertising stimulates demand for a generic category of a product, as dairy products. It is used in these two sttuations : First, as piineering advertising when a product is first introduced. This type of ad informs rather than persuades, emphasizing product benefits- not its brand name (as backround stellite dishes for TVs or stereo lazer discs) Selective demand advertising is competitive advertising as in comparative ads. Major Types of Media and Adventages and Disadventages Broadcast Media : Television is a very important mass media. Its adventages is that it reaches a widely diversified audience. It creates opportunities for demons tration. Newspapers are flexible, timely, widely read, have low circulation costs and short advertisement life-span. Magazines are good foi" high quality printing, reaching a national market at low cost, reaching a selected audience with minimal waste circulation, and are not good because of their inflexibility and infrequent market exposure. Radio; biggest adventages is its low cost and ability to pinpoint market segments, but a disadventage in that it is only an audio impression. -VIII- Outdoor; a flexible, low cost medium, but waste circulation will occur unless it is a widely used consumer good. CHAPTER 2 : Outdoor Advertising Out door or out of home advertising is flexible, low cost medium that takes in a variety of ad mechanisms : Skywritting, bus shelters, taxi cabs, giant inflatables, costmction site fences, mini-billboards in malls, lighted moving signs in bus terminals and airports, ads painted on the sides of cars ans trucks, all fall under the out of home umbrella, but the ubiquitous billboard is the leading example of medium. Outdoor advertising is growing both in terms of coverage and popularity. There are three major types of outdoor advertising : 1. Posters 2. Painted bulletins 3. Spectaculars And the other are bleed posters, electrical sign, aerial advertising (for ex. big ballons, skywritting, kated etc.) The outdoor advertising messages reach all of social-economic groups. So they haven't demographic selectivities. Transit Advertising : In many times it is in the outdoor advertising but some countries seperate them into different groups. The types of transit advertising are : a. Car cards b. Outside displays c. Station posters -IX- Car cards are usually inside vehicles. Outside displays are location outside of vehicles. (Generally bus or metrovagon) Station posters like a outdoor posters but at generally placed in or around of train station, bus stop, subway station or airport. Outdoor Advertising in Turkey There are many types of outdoor advertising in our country but there is a few standardizations types of these. A few company rent poster panels (billboard panels). The new outdoor advertising is posterpano advertising. It is used for electric pillar. CHAPTER 3 : EVALUATING THE ADVERTISING EFFORT Evaluating advertising is important to top management. It is difficult to measure the effectiveness of advertising. There two methods used to measure advertising effectiveness. First measuring sales results. And second is measuring advertising's comunication performance. Fisr; measure sales directly related to the advertisment. At the second are use to readership, recognition and recall tests. Marketers often set advertising objectives based on the comunication effects of a campaign. This enables them to evaluate advertising effectiveness in terms of psyhologically defined steps of behavior that are assumed to lead eventually to a product's purchase. The methods use to measure effectiveness : Readership survey. Recognition and recall tests (for ex. Starch readership rapports, discusion groups, inquiry tests), projective techniques (assocation of word or sample, psychogalvanic techniques, tachtoscope etc.). Measurement of attitudes could be used to measure advertising effectiveness. CHAPTER 4: This chapter includes two main research. One of them is interviews to six advertising agencies. Interviews are about the outdoor advertising in Turkey and comparative to other of advertising. The second research is formed of questionnaire form. This form application for 250 person in different region of Istanbul. The research objective is measure of outdoor advertising communication performance. Some results of research are as follows: - 16 % of sample size don't look to billboard. - Slogan remembering ratio is not very high. On an average, two slogans are remembered in eighth slogans. At the same time, level of telling billboard advertising that is remembered by the audience is not very good. These show that, billboard advertising communication performance don' t high enough. However, billboard important for new product advertising campaign. Audience think that these are effective for the new product to introduce to market. Billboard advertising is also effective to provide, a new product that is advertised on billboards, is tested by audience ( a specially by women ). Most important result of the research is that slogan remembering ratio and the level of telling billboard advertising is not related demographic characteristics.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Reklamcılık; İşletme; Reklam etkinliği; Reklamlar; Advertising; Business administration; Advertising effectiveness; Advertisements